(untitled) - Miller, Wilma H. (San Francisco, CA, 2005)
Improving Early Literacy offers teachers an arsenal of reading strategies for helping struggling emergent readers develop letter-name knowledge, sight word knowledge, phonics, and reading fluency skills. This book provides a comprehensive listing of various strategies incorporated into activities and worksheets and offers
Keywords: Language arts (Elementary),Language arts,Nghệ thuật ngôn ngữ ( sơ cấp ),Nghệ thuật ngôn ngữ; Activity programs,Remedial teaching,Khắc phục giảng dạy